DOES WORK-LIFE BALANCE IMPACTS JOB SATISFACTION: EVIDENCE FROM FACULTY MEMBERS - Dr. P. Jyothi, Dr. C. Sonia, Dr. B. Rajasekar, D. Krishnamoorthy, S. Ramanathan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This research paid attention on faculty members of engineering colleges belongs to Tamilnadu State. The study engaged descriptive research design and the faculty members of engineering colleges, classified in to professor, associate professor and assistant professor are interest of population. The primary objective of study was to analyze the impact of work life balance (WLB) on job satisfaction (JS) among faculty members of engineering colleges. Samples were drawn using stratified random sampling technique to make sure samples are impartially chosen and to minimize sample selection biasness. Data collection was done through questionnaire and face to face interviews. The study was intended to discover whether family support and management support affects work life balance of the respondents and in turn how work life balance affects job satisfaction. in data analysis, initially using kurtosis and Skewness test and Cronbach Alpha test was carried out to check the normality distribution and reliability of data. Two statistical techniques bivariate correlation analysis and multiple regression analysis were applied to analyze the impact of work life balance on job satisfaction. Results of bivariate correlation analysis indicates the positive relation among work life balance and job satisfaction and multiple regression analysis results reveal that among two variables of work life balance, management support is the variable which brings high variance in job satisfaction. The results of the study were supported and proved by previous researchers, who carried out their research on similar association.